Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Pelecehan Seksual - Nurjaini Nurjaini; Mar’ie Mahfudz Harahap (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
This research analyzes the legal protection for child victims of sexual abuse in Indonesia. Using a normative approach and literature review, this study aims to understand the legal protection provided to child victims of sexual abuse, the factors influencing sexual abuse against children, and efforts to prevent such criminal acts. The research reveals that Indonesia has a responsibility to protect child victims of crimes. Law Number 35 of 2014 on Child Protection provides the basis for protection, including the rights of children, protection from violence and discrimination, and the fulfillment of their dignity. Special protection is given to child victims of sexual abuse through rehabilitation, protection of the victim's identity, safety guarantees for victim witnesses, and accessibility to case developments. Criminal punishment for perpetrators of child sexual abuse is regulated by laws and the Criminal Code. In handling cases of sexual abuse, the role of forensic medicine is crucial in gathering necessary evidence. The principle of diversion is also applied in handling cases involving juvenile perpetrators of sexual violence. Serious coordination among the police, prosecutors, and judges is required to eradicate sexual abuse crimes against children. In conclusion, this research presents an overview of the legal protection for child victims of sexual abuse in Indonesia. Ongoing efforts are being made to strengthen protection and prevent these crimes through inter-agency coordination and effective law enforcement